2010
DOI: 10.1002/chem.201000104
|View full text |Cite
|
Sign up to set email alerts
|

Good Timing in Total Synthesis: The Case of Phoslactomycin A

Abstract: The importance for the right order of functional group introduction and manipulation (good timing) was demonstrated in the course of a total synthesis of phoslactomycin A. The synthetic strategy comprised a Cu(I)-thiophene carboxylate (CuTC, Liebeskind's reagent)-mediated coupling to introduce the Z,Z-diene at the final stage of the synthesis in the presence of a protected phosphate. Key features for the assembly of the C1-C13 fragment were an asymmetric dihydroxylation, an Evans-aldol reaction and an advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…18 The regioselective arene borylation reaction has been used as a key step in natural product synthesis 19. One task of interest for the fulicineroside project was the optimal timing20 for the borylation step (Figure 2). Earlier experiments21 had shown that the iridium‐catalyzed borylation of a benzofuran 36 results in an attack at the neighboring position to the dibenzofuran oxygen atom, which is not appropriate to the present strategy.…”
Section: Resultsmentioning
confidence: 99%
“…18 The regioselective arene borylation reaction has been used as a key step in natural product synthesis 19. One task of interest for the fulicineroside project was the optimal timing20 for the borylation step (Figure 2). Earlier experiments21 had shown that the iridium‐catalyzed borylation of a benzofuran 36 results in an attack at the neighboring position to the dibenzofuran oxygen atom, which is not appropriate to the present strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Reductive work-up with PPh 3 gave the aldehyde, and then the Wittig olefination with excess NaHMDS-ICH 2 PPh 3 I afforded the key central core (+)-19 as a single Z-isomer in 70% yield over two steps. 21 With the central core (+)-19 and side chain (+)-18 in hand, a modified Negishi reaction afforded the desired (+)-17 in 77% yield. Then, desilylation using p-TsOH furnished alcohol (+)-33 in 89% yield.…”
Section: Total Synthesis Of Epiplakinic Acid Fmentioning
confidence: 99%
“…D M P , C H 2 Cl 2 , pyr alkenes, 81,84,92,106,[160][161][162][163][164][165] dienes, 92,166 alkynes, 160 tertiary alcohols, 106 ethers, 92,94,161,162,164,166,167 aldehydes, 92 a,b-unsaturated ketones, 92 esters, 98,166 a-hydroxy esters, 168 amides, 166 lactones, 161 a,bunsaturated lactones, 92,165 macrolactones, 114 lactams, 168 carbamates, 98 amines, 168 alkyl halides, 94 phosphates, 165 azides, 165 acetals, 81,88,106,160 sulfides, 81 and epoxides. 84 Scheme 2 77,83,85,[89][90][91][92]…”
mentioning
confidence: 99%
“…DMP, CH 2 Cl 2 , pyr ROTMS, 165,167 ROTBS, 84,94,160,166 ROTES, 81,84,160,166 ROTBDPS, 81,84,94,160 ROTIPS, 81,94,165 ROMe, 84,166 ArOMe, 168 ROBn, 106,160 ROPMB, 81,84,165 ROAlloc, 84 ROBec, 84 ROMOM, 106,168 silyl acetal, 167 and R 2 NBoc. 98 Although DMP tolerates several functional groups, Grieco and Piñeiro-Nuñez reported that the oxidation of a hydroxy carboxylate intermediate (formed by ring opening the corresponding lactone) was best performed with the less popular fluorinated iodine(V) compound.…”
mentioning
confidence: 99%
See 1 more Smart Citation